Satisfacción al cliente de la Empresa Colombatti en la ciudad de Babahoyo, periodo 2023. - Gonzales Cando, Danny Alberto (2024)
The case study conducted at the Colombatti company, whose objective is to analyze the level of customer satisfaction, focused on evaluating the sales process, customer service and overall customer satisfaction. Through interviews and surveys, several deficiencies in sales management and customer service were identified. The problems of the study focused on Colombatti's sales process and customer service, which were deficient and disorganized. The lack of a standardized and efficient sales process led to inconsistencies and inadequate follow-up on sales opportunities. In addition, the absence of strategies to identify and classify customers negatively affected service. Informal interactions dependent on the personal style of each salesperson generated inconsistent experiences. Reactive and disorganized complaint handling increased customer dissatisfaction and loss of loyalty. The results of the study showed that, although some aspects such as staff knowledge and product quality were perceived positively, there were critical areas for improvement. These areas included staff training, product quality control, after-sales service and the overall shopping experience. It was concluded that the lack of adequate staff organization and training, along with the lack of a standardized sales process, were the main factors contributing to low customer satisfaction and lost sales opportunities at Colombatti during 2023. Addressing these areas for improvement is essential to increase customer satisfaction, improve the efficiency of the sales process and strengthen the company's competitive position.